Dokumentarisch Arbeiten 2 (I-II) - Hübner, Christoph (Germany, 1998)
Four documentary filmmakers, four talks, four key players of the German documentary film movement since the 60s: Hans-Dieter Grabe, Elfi Mikesch, Harun Farocki und Thomas Heise. Each of them has developed an own approach to filmmaking and a personal style. Christoph Hübner, a documentary filmmaker himself, succeeds in portraying four very different personalities, their works and their theories. Illustrated with excerpts from their films.
The discs contain four parts: Christoph Hübner talks with Hans-Dieter Grabe 1998, (64 min.), Christoph Hübner talks with Elfi Mikesch 2000, (60 min.), Christoph Hübner talks with Harun Farocki 2005, (60 min.), Christoph Hübner talks with Thomas Heise 2012, (59 min.).
Options for subtitles: English, French, Spanish, Portuguese.
Keywords: Documentary films